Distinct features of two lipid droplets types in cell nuclei from patients with liver diseases - Norihiro Imai; Yuki Ohsaki; Jinglei Cheng; Jingjing Zhang; Fumitaka Mizuno; Taku Tanaka; Shinya Yokoyama; Kenta Yamamoto; Takanori Ito; Yoji Ishizu; Takashi Honda; Masatoshi Ishigami; et al. (Scientific Reports, 2023)
Abstract Lipid droplets (LDs) have been observed in the nuclei of hepatocytes; however, their significance in liver disease remains unresolved. Our purpose was to explore the pathophysiological features of intranuclear LDs in liver diseases. We included 80 patients who underwent liver biopsies; the specimens were dissected and fixed for electron microscopy analysis. Depending on the presence of adjacent cytoplasmic invagination of the nuclear membrane, LDs in the nuclei were classified into two types: nucleoplasmic LDs (nLDs) and cytoplasmic LD invagination with nucleoplasmic reticulum (cLDs in NR). nLDs were found in 69% liver samples and cLDs in NR were found in 32%; no correlation was observed between the frequencies of the two LD types. nLDs were frequently found in hepatocytes of patients with nonalcoholic steatohepatitis, whereas cLDs in NR were absent from the livers of such patients. Further, cLDs in NR were often found in hepatocytes of patients with lower plasma cholesterol level. This indicates that nLDs do not directly reflect cytoplasmic lipid accumulation and that formation of cLDs in NR is inversely correlated to the secretion of very low-density lipoproteins. Positive correlations were found between the frequencies of nLDs and endoplasmic reticulum (ER) luminal expansion, suggesting that nLDs are formed in the nucleus upon ER stress. This study unveiled the presence of two distinct nuclear LDs in various liver diseases.